Internet (Web) Protection of Accounting Information - Denchev, Emil (Research Papers, 2005)
Connection of business to Internet Technologies gives a lot of additional advantages but it leads to some risk. Risk connected with the possibility of unestablishe remote access to shared Accounting Information (AI) and access to the AI send by the connecting channels of company network, based on the Internet.Programmer MethodsThey include the use of:Password for access to the shared AI on the network. Concerning the passwords, observance of the International Security Standard C2 requirements is recommended,Determination of rights for remote access to the shared AI. These rights are defined on the level of a user (a chief accountant) or a group of users (Accountants, cashiers, material responsible staff, administrators),Archiving of the AI in virtual time – on-line archiving is means of the AI protection from destructions caused by technical reasons. It is carried out on the Internet on a server disk of data, On-live updating of anti-virus programs (Live Update). Companies that have worked out the antivirus programs, offer on-line (live update) files updating with virus definitions,Updating of the operating system (Update). The aim is eliminate the critical punches of the system security,Protective walls (Firewall). They are means of the AI protection in the company computer network, based on the Internet attacks from outside and inside.Virtual Private Networks (VPN). They are used for dependable connection of the company to its branches using the Internet. The aim is to process and send the AI.On-line scan of workplace. It is done on purpose of testing the system security ability. Microsoft Baseline Security Analyzer (MBSA) has been developed on purpose of evaluation of the protection degree of one or more computers from the VPN based on Windows. MSBA determines if the built-in security systems are outdated and had better be updated;Cryptographic MethodsCryptographic methods for the AI protection are applied while sending the information by the connecting channels. One of the technologies for the AI cryptography used in the Republic of Bulgaria is Public Key Infrastructure (PKI). Confidentiality, attestation of senders identify, AI completeness and protection from repetition are realized by this technology.Legal MethodsLegal methods for the AI Internet Protection are based on the existing normative base in the Republic of Bulgaria, including:Electronic Documents and Signatures Protective LawCriminal Procedure Code;Technical MethodsTechnical methods for the AI Internet Protection include technical methods for access restriction to the AI as:Smart cardsHardware realized protective walls (Hardware Firewall).